FeNO and Asthma Treatment in Children. Issue 4 (January 2015) - Lu, Min; Wu, Beirong; Che, Datian; Qiao, Rong; Gu, Haoxiang; Wang., Yong
<x xml:space="preserve">Abstract</x> Abstract Traditional asthma treatments are typically adjusted in children with asthma using symptoms and spirometry. Treatments tailored in accordance to inflammatory markers, such as fraction of exhaled nitric oxide (FeNO) or sputum eosinophils, are increasing in use. This meta-analysis evaluated the potential benefit of incorporating the use of monitoring FeNO with guideline-based management in treating children with asthma. PubMed and Cochrane CENTRAL databases were searched until November 2013 for randomized control trials that investigated the use of FeNO compared with conventional monitoring in managing asthma in children. Included studies had at least 2 intervention groups: one that utilized FeNO and the other that utilized only conventional or standard methods (eg, spirometry, symptoms, and others) to guide treatment. Six studies were included in the meta-analysis comprising 506 subjects whose treatment was monitored using FeNO and 511 subjects who were managed using conventional methods. We found no difference between the FeNO and the conventional groups in FeNO value (95% confidence interval [CI]: −0.31, 0.1), change from baseline in FEV1 (95% CI: −0.07, 0.20), or steroid use (95% CI: −0.67, 1.80). However, the FeNO group was associated with a lower frequency of >1 asthma exacerbation (95% CI: 0.532, 0.895). This meta-analysis suggests that using FeNO to guide treatment decisions has little clinical benefit, although may result in a decrease in asthma exacerbations. Our findings support the use of guideline-based asthma management and diagnosis.